Notes From The Couch: Novel Spaces for Creation in Coronavirus-era Choral Music Education - Menard, Laura (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
As Michel Serres states, “The one who has power is the one who has the source and emission of sound” (1982). The sudden soundlessness of our COVID-19 existence is one of the largest pandemic challenges facing musicians. While some argue that there should be a hiatus on creation, others are embracing music’s adaptations to less traditional forums and formats. As a public high school teacher and conductor-educator with a youth-focused private organization, I am experiencing first-hand the improvisations, challenges, triumphs—and attendant burn-out—of rapidly adapting new spaces in which to keep my musical communities intact. Fellow conductor-educators near and far, working with populations at all ages and stages, are also bravely forging onward, rejecting sound-less and ensemble-less realities by adapting online. This all begs the questions: What does the near future hold for choral singing? And what will singing ensembles look like on the other side of current restrictions? Drawing together personal experience, informal interviews, explorations of the transformations of public and private space, sound and media studies, drift methodology, and the proliferation of recent articles in news and arts media, this essay investigates the novel spaces being created by and for choral arts educators amidst the uncertainties of what new reality awaits us on the other side of the screen-scape.